Borrowing in Western financial markets by Eastern European countries - Hans-Eckart Scharrer; Klaus Bolz (Intereconomics, 1979)
What are the borrowing strategies and practices of European members of the Council for Mutual Economic Assistance (CMEA)? The authors had extensive discussions with bankers in the leading financial centres in Europe. Some of their findings are presented in the following article.
Keywords: 330; CMEA